Relationship between football-specific training characteristics and tibial bone adaptation in male academy football players - Wrona, H. L.; Zerega, R.; King, V. G.; Reiter, C. R.; Odum, S.; Manifold, D.; Latorre, K.; Sell, T. C. (Sports, 2023)
Clinicians frequently assess asymmetry in strength, flexibility, and performance characteristics as a method of screening for potential musculoskeletal injury. The identification of asymmetry in countermovement jumps may be an ideal method to reveal asymmetry in other lower extremity characteristics such as strength that otherwise may require additional testing, potentially reducing the time and burden on both the athlete and clinicians. The present study aims to examine the ability of asymmetry in both the single-leg and two-leg countermovement jump tests to accurately detect hip abduction, hip adduction, and eccentric hamstring strength asymmetry. Fifty-eight young male elite soccer players from the same professional academy performed a full battery of functional performance tests which included an assessment of hip adductor and abductor strength profiles, eccentric hamstring strength profiles, and neuromuscular performance and asymmetries during countermovement jumps. Bilateral variables attained from both the single-leg and two-leg countermovement jump tests included concentric impulse (Ns), eccentric mean force (N), and concentric mean force (N) computed by the VALD ForceDecks software. Average maximal force (N) was calculated bilaterally for the strength assessments. Asymmetry was calculated for each variable using 100 × |(right leg - left leg)/(right leg)| and grouped into three categories: 0 to <10%, 10% to <20%, and 20% or greater. Analyses were performed for the two higher asymmetry groups. The accuracy to detect strength asymmetry was assessed as the sensitivity, specificity, and predictive values for positive and negative tests. The outcomes from the accuracy assessments suggest that the single-leg countermovement jump concentric impulse variable at the 20% threshold is indicative of a youth male soccer player having hip adduction strength asymmetry while also demonstrating more accuracy and applicability than the two-leg countermovement jump concentric impulse variable.